2021
DOI: 10.18231/j.ijmmtd.2021.029
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of candida infection among intensive care unit patients and their susceptibility profile

Abstract: species are responsible for causing many health care associated and central line associated infections. They are responsible for causing opportunistic infection in human beings. Genus of is composed of a heterogeneous group of organsims.Invasive infections of mainly caused by , , & . The main objective of this study was to isolates and Non- albicans and their antifungal susceptibility testing.Thestudy was carried out in the Department of Microbiology, in Tmu Hospital Moradabad. Total numbers of 806 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Among Non-albicans Candida, Candida tropicalis was the most common species isolated followed by C. albicans, C. glabrata and C. parapsilosis respectively. Our results were in accordance with the studies done by D. Kumar et al 17 Lata R Patel et al 18 and Ayushi Jain et al 19 which revealed C. tropicalis as the most prevalent species. among the Candida isolates.…”
Section: Discussionsupporting
confidence: 93%
“…Among Non-albicans Candida, Candida tropicalis was the most common species isolated followed by C. albicans, C. glabrata and C. parapsilosis respectively. Our results were in accordance with the studies done by D. Kumar et al 17 Lata R Patel et al 18 and Ayushi Jain et al 19 which revealed C. tropicalis as the most prevalent species. among the Candida isolates.…”
Section: Discussionsupporting
confidence: 93%